Hukum Islam: Khitabullah Atau Rasionalisme - Efizal Anwar (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2014)
This article presents about Islamic law which functions as a guide as well as a protector for human being to live in the world and in the judge Day. Islamic Law is a set of rules on a manner of a mukallaf dealing with the relation of human beings to their Creater, and the relation of human beings one another. One of the rules is irrational or t’abbud in which human beings only obey it based on syar’i without asking how did it come. Then, there is a t’aqquli law by which human beings can only judge maslahat within the law so that it can be changed in accordance with the progress of era.